TEKNIK ASSERTIVE TRAINING SECARA DARING UNTUK MENINGKATKAN SELF ESTEEM SISWA KELAS VII SMP NEGERI 2 SOREANG - Nanin Rahmatyana; Heris Hendriana; Riesa Rismawati Siddik (IKIP Siliwangi, 2021)
Self-esteem is a form of individual assessment of himself as an individual who has the ability, meaning, value and competence. Stepping on the transition period from elementary school to junior high school, every individual needs an adjustment to the new environment, one of which is that each individual must be able to show good behavior in the community, but if the individual has not been able to assess how far the individual assesses himself then will have an impact on the emergence of conflicts that come from within him and judge something irrationally which will have an impact on emotional disturbances that can affect his relationships with other people. The purpose of this study is that students are able to assess themselves, be able to socialize and be able to communicate well. This study uses descriptive qualitative by analyzing existing data by describing in detail. This study uses respondents totaling 6 seventh grade students at SMP Negeri 2 Soreang by looking at the results of observations that have been made tend to have self-esteem low. For this reason, it is necessary to provide BK services withtechniques assertive training for 3 meetings via video calls media WhatsApp which are supported by the results of interviews and observations showing changes from within students who are able to assess themselves, are able to think positively and can adapt well.Keywords: Assertive Training Techniques, Self Esteem